The Influence Of Career Development, Training, And Communication On Employee Performance At The Nusantara Sakti (NSS) Dealer In Bengkulu City - Merta Kusuma; Dinda Ermnaya Novaliza (UNIVED Press, 2024)
The purpose of this research is to find out the influence of Career Development, Training and Communication on Employee Performance at the Nusantara Sakti (NSS) Dealer in Bengkulu City. The population in this study were all employees of the Bengkulu City Dealer Nusantara Sakti (NSS), totaling 36 people and sampling using the saturated sampling method. In this study the researcher used data collection methods by means of observation, interviews and distributing questionnaires.The data analyzed using the instrument tests , classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, hypothesis testing and analysis of the coefficient of determination. The results showed that career development had a positive and significant effect on the employee performance, then training had a positive and significant effect on the employee performance and communication had a negative and insignificant effect on the employee performance due to a lack of communication between superiors and subordinates as well as fellow co-workers. So, from the results of the research,it can be concluded that career development, training and communication have a simultaneous effect on employee performance at Nusantara Sakti (NSS) Dealer of Bengkulu City. While partially the communication variable has no effect on employee performance at Nusantara Sakti (NSS) Dealer of Bengkulu City.